Reconstructing the Identity of Chinese Shu Embroidery in Contemporary Product Design: A Psycholinguistic Approach to Cultural Semiotics and Consumer Perception - Han, Yang; Leepanuwong, Ruttiporn; Bunyasakseri, Thirawut (Forum for Linguistic Studies, 2025)
This study explores the evolving identity of Chinese Shu embroidery in contemporary product design through the Sapir–Whorf Hypothesis, also known as linguistic relativity. Shu embroidery, a traditional Chinese art form renowned for its rich symbolic meanings and cultural expressions, is increasingly incorporated into modern consumer products. However, these adaptations often lead to shifts in the interpretation and perceived identity of Shu embroidery, particularly among international audiences. By applying the linguistic relativity framework, this research investigates how different consumer groups interpret the cultural meanings embedded in Shu embroidery, expressed through symbolic motifs, patterns, and design narratives. The study combines qualitative visual analysis, semi-structured interviews, and consumer perception surveys to examine how language, cultural framing, and symbolism influence consumer understanding and emotional connection to these designs. The findings reveal that consumers from varying linguistic and cultural backgrounds perceive the same symbolic cues differently. Native Chinese speakers often decode motifs through culturally inherited semantic structures, while global consumers interpret them through more generalized or aesthetic lenses. This divergence highlights the need for a more culturally sensitive design strategy to accurately reconstruct Shu embroidery’s identity for a global market. This study proposes a semiotic-informed, culturally adaptive framework for heritage product design that respects linguistic diversity, preserves cultural integrity, and enhances cross-cultural communication, offering valuable insights for designers and heritage product developers.